Compartmentalization of Incompatible Polymers within Metal–Organic Frameworks towards Homogenization of Heterogeneous Hybrid Catalysts for Tandem Reactions. Issue 39 (19th June 2018) - Zhao, Jin‐Hao; Yang, Yong; Che, Jin‐Xin; Zuo, Jun; Li, Xiao‐Hua; Hu, Yong‐Zhou; Dong, Xiao‐Wu; Gao, Liang; Liu, Xin‐Yuan
Abstract: New catalytic systems that contain incompatible catalytic sites were constructed by the in situ polymerization of acidic and basic polymers into metal–organic frameworks, which resulted in highly porous, recyclable, and durable catalytic composites with excellent compartmentalization, so that opposing agents were spatially isolated. These synthesized hybrid catalysts exhibited excellent catalytic activity for one‐pot "wolf and lamb" reactions (deacetalization/Knoevenagel or Henry), which was attributed to their unique characteristic of having a locally homogeneous, but globally heterogeneous, structure. Abstract : Who cried wolf? A new catalytic system that combines multiple incompatible catalytic sites is developed, and it is shown to exhibit excellent catalytic activity for one‐pot "wolf and lamb" reactions.